2022
DOI: 10.1097/lgt.0000000000000691
|View full text |Cite
|
Sign up to set email alerts
|

Endocervical Margins Status in Excision for Preventing Cervical Cancer According to the Transformation Zone Type

Abstract: The aim of this study is to assess the outcomes of 610 excision types I and II in a referral facility as a function of transformation zone (TZ) types.Methods: This is a retrospective cohort study of women with cervical precursor lesions who underwent loop electrocautery excision procedure from 2017 to 2019 at the University of Campinas. The primary outcome was endocervical margin status, negative or positive. Other variables were excision type (I/II), TZ (1/2/3), age, menopausal status, hormonal contraceptives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Other studies indi-Life 2023, 13, 1775 7 of 11 cate factors like older age, multiparity and disease severity associated with endocervical margin positivity [13,31]. Gertrudes L. et al found that an excision length between 10 and 15 mm was associated with a significantly higher chance (with a calculated OR of 2.01) of obtaining clear endocervical margins in women with a TZ 1, even though the overall rate of clear endocervical margin was observed in three out of four patients regardless of performed excision length [12]. This aligns with our findings demonstrated in Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies indi-Life 2023, 13, 1775 7 of 11 cate factors like older age, multiparity and disease severity associated with endocervical margin positivity [13,31]. Gertrudes L. et al found that an excision length between 10 and 15 mm was associated with a significantly higher chance (with a calculated OR of 2.01) of obtaining clear endocervical margins in women with a TZ 1, even though the overall rate of clear endocervical margin was observed in three out of four patients regardless of performed excision length [12]. This aligns with our findings demonstrated in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Since an excisional treatment of removing more than 10 mm cervical tissue is known to be an independent risk factor for adverse pregnancy events, we chose to compare two subgroups with a cut-off value of 10 mm to provide data for informed patient education, particularly for women of childbearing age with a desire to get pregnant [ 15 ]. Given the fact that an involved endocervical margin is especially known to be a predictor for treatment failure, i.e., persistent disease, we chose to evaluate only the endocervical margin status [ 12 , 22 ]. Endocervical margin positivity was referred to histological confirmation of HSIL or carcinoma on the surgical margin and designated as “involved” or “clear”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation